Regional distribution of HLA frequencies in the USA: implications for TCR-based therapies - Dirk Nagorsen; Christian Roy; Tomasz Sewastianik; Ileana Saenz; Gregory J Opiteck; Sean Stagg; Martin Maiers (Journal for ImmunoTherapy of Cancer)
Understanding regional distribution of HLA frequencies is crucial for optimizing enrollment in HLA-restricted clinical trials and to promote trial diversity per the Food and Drug Administration’s 2020 mandate. Using US HLA frequency data and census demographics we developed a method to create high-resolution HLA class 1 genotypic frequency maps. Analyzing HLA-A*11:01 and HLA-B*58:01 as alleles of interest, we found significant US regional variations. HLA-A*11:01, which presents KRAS neoantigen mutations targeted by TCR T-cell therapies, showed 10–15% genotypic frequency (national average 11.2%), with western US states 1.5 times higher than average and local variations within California (10–19%). These insights can be used to guide clinical trial site selection, for example, in National Cancer Institute (NCI) cancer center catchment areas. For HLA-B*58:01, which reacts pharmacogenetically with allopurinol and results in severe cutaneous adverse reactions, Mississippi had a high frequency among US states, which could be used to guide potential public safety campaigns. This method can identify regions with high HLA type representation, aiding efficient patient identification and enrollment for HLA-specific clinical trials and health-awareness efforts.